2013
DOI: 10.1186/1471-2164-14-845
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of porcine backfat and intramuscular fat fatty acid composition using high-density genotyping and expression data

Abstract: BackgroundPorcine fatty acid composition is a key factor for quality and nutritive value of pork. Several QTLs for fatty acid composition have been reported in diverse fat tissues. The results obtained so far seem to point out different genetic control of fatty acid composition conditional on the fat deposits. Those studies have been conducted using simple approaches and most of them focused on one single tissue. The first objective of the present study was to identify tissue-specific and tissue-consistent QTL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 44 publications
1
59
0
Order By: Relevance
“…Multiple regions were found that had a high frequency of ROH across both the maternal breeds whereas one region was detected across all three breeds. The regions on SSC1 (248.7–264.2 Mb), SSC4 (42.1–61.3 Mb) and SSC14 (98.0–111.7 Mb) detected in LW and LA were previously shown to impact meat and carcass quality [4851], multiple production and meat quality traits [52, 53], and reproduction [54], respectively. Four regions were found to have a higher frequency of ROH5 and/or ROH10 across the terminal DU breed and both the maternal breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple regions were found that had a high frequency of ROH across both the maternal breeds whereas one region was detected across all three breeds. The regions on SSC1 (248.7–264.2 Mb), SSC4 (42.1–61.3 Mb) and SSC14 (98.0–111.7 Mb) detected in LW and LA were previously shown to impact meat and carcass quality [4851], multiple production and meat quality traits [52, 53], and reproduction [54], respectively. Four regions were found to have a higher frequency of ROH5 and/or ROH10 across the terminal DU breed and both the maternal breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Four regions were found to have a higher frequency of ROH5 and/or ROH10 across the terminal DU breed and both the maternal breeds. The regions on SSC3 (36.4–59.5 Mb) and SSC14 (121.0–132.5 Mb) were found to be associated with meat and carcass quality traits [52, 55, 56], and with carcass quality [57] and fitness traits [58], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts from the Pig Genome Sequencing Consortia in assembling the pig genome materialized in a new and efficient tool in the form of genome browsers that can help to identify positional candidate genes underlying these relevant genomic regions. The latest GWAS studies in IMF composition have confirmed the relevance of regions in SSC4, 8 and 14 across most breeds and identified other breed-specific fragments [20,40,41]. On the whole, GWAS regions explain in most cases a relatively small fraction (<8%) of the phenotypic variation.…”
Section: The Molecular Basis Of Imf Content and Compositionmentioning
confidence: 95%
“…This limits the application of these markers in a pig breeding system that has lean content, among other traits, as a selection objective. Similarly, genomic regions associated with fat composition are mostly shared between muscle and fat traits [41], indicating that common fatty acid enzymatic/transport pathways take place in these two fat depots [45]. In terms of fatty acid composition this is not a limitation, as long as the lean content remains the same.…”
Section: The Molecular Basis Of Imf Content and Compositionmentioning
confidence: 99%
See 1 more Smart Citation